Green Supply Chain Management: uma análise da produção científica recente (2001-2012) - Sehnem, Simone; Jabbour, Charbel José Chiappetta [UNESP]; Rossetto, Adriana Marques; Campos, Lucila Maria De Souza; Sarquis, Aléssio Bessa (Associação Brasileira de Engenharia de Produção, 2014)
The goal of this study was to analyze international scientific production in the area of constant-production green supply chain management from 2001 to 2012 using the Business Source Complete database (EBSCO Host). The database was checked for cooperation between authors and institutions, author entrants, production and continuity categories, regularity of publication and distribution of publications over time. Ninety articles were included in the sample, and the results showed a reduction in the number of publishing authors, concentrated in one-timers category with 68.90%. The highest yield for a single author was 10 articles, and the most prolific periodical was the Journal of Cleaner Production, with 12 articles published on the subject. Clark University (USA) stood out in terms of output, with 12 affiliated authors. It was concluded that the subject had experienced a significant rise in published literature over that time period.

O objetivo deste estudo foi analisar a produção científica internacional na área de Green Supply Chain Management constante de produções da base de dados Business Source Complete (EBSCO Host) no período de 2001 a 2012. Pôde-se verificar a estrutura de cooperação entre autores e instituições, os autores entrantes, as categorias de produção e continuidade, a regularidade de publicação e a distribuição das publicações ao longo do tempo. Noventa artigos compuseram a amostra e os resultados evidenciaram que o número de autores que publicam é reduzido, concentrados na categoria one-timers, com 68,90%. A maior produção foi 10 artigos por autor e o periódico mais prolífico foi o Journal of Cleaner Production, com 12 artigos publicados sobre o assunto. A Clark University (USA) destaca-se com 12 autores filiados. Conclui-se que a temática teve uma ascensão expressiva nos últimos anos.
Green Supply Chain Management: a review of recent scientific production (2001-2012)
Keywords: Green Supply Chain Management; Gestão verde da cadeia de suprimentos; Bibliometria; Categorias de produção e continuidade; Green Supply Chain Management; Management of green supply chains; Bibliometrics; Categories of production and continuity